Overall survival with sacituzumab govitecan in hormone receptor-positive and human epidermal growth factor receptor 2-negative metastatic breast cancer (TROPiCS-02): a randomised, open-label, multicentre, phase 3 trial - Rugo, Hope S.; Bardia, Aditya; Marmé, Frederik; Cortés, Javier; Schmid, Peter; Loirat, Delphine; Trédan, Olivier; Ciruelos, Eva; Dalenc, Florence; Gómez Pardo, Patricia; Jhaveri, Komal L; Delaney, Rosemary; et al. (The lancet, 2023)
Background - Sacituzumab govitecan demonstrated significant progression-free survival benefit over chemotherapy in the phase 3 TROPiCS-02 trial in patients with pretreated, endocrine-resistant hormone receptor-positive, human epidermal growth factor receptor 2-negative (HR+ and HER2-) metastatic breast cancer with limited treatment options. Here, we report the protocol-specified final analysis of overall survival and endpoints by trophoblast cell-surface antigen 2 (Trop-2) expression and other variables. - Methods - In this randomised, open-label, multicentre, phase 3 trial, which took place in 91 centres across North America (the USA and Canada) and Europe (Belgium, France, Germany, Italy, the Netherlands, Spain, and the UK), patients were randomly assigned (1:1) to receive sacituzumab govitecan or chemotherapy (eribulin, vinorelbine, capecitabine, or gemcitabine). Patients had confirmed HR+ and HER2- locally recurrent inoperable or metastatic breast cancer and had received at least one previous endocrine therapy, a taxane, and a CDK4/6 inhibitor in any setting and two to four previous chemotherapy regimens for metastatic disease. The primary endpoint was progression-free survival (previously reported and not included in this analysis), and secondary endpoints included overall survival, objective response rate (ORR), and patient-reported outcomes. Overall survival was assessed using stratified log-rank tests and Cox regression. Trop-2 expression was assessed in tumour tissue by immunohistochemistry. In the statistical testing hierarchy, ORR and patient-reported outcomes were tested sequentially if overall survival was significant. This study is registered with ClinicalTrials.gov, NCT03901339. - Findings - At the data cutoff date of July 1, 2022, 543 of 776 screened patients were randomly assigned between May 30, 2019, and April 5, 2021, with 272 patients in the sacituzumab govitecan group and 271 patients in the chemotherapy group. With a 12·5-month (IQR 6·4-18·8) median follow-up, 390 deaths occurred among 543 patients. Overall survival was significantly improved with sacituzumab govitecan versus chemotherapy (median 14·4 months [95% CI 13·0-15·7] vs 11·2 months [10·1-12·7]; hazard ratio [HR] 0·79, 95% CI 0·65-0·96; p=0·020); survival benefit was consistent across Trop-2 expression-level subgroups. ORR was significantly improved with sacituzumab govitecan compared with chemotherapy (57 [21%] patients vs 38 [14%]; odds ratio 1·63 [95% CI 1·03-2·56]; p=0·035), as was time to deterioration of global health status and quality of life (median 4·3 months vs 3·0 months; HR 0·75 [0·61-0·92]; p=0·0059) and fatigue (median 2·2 months vs 1·4 months; HR 0·73 [0·60-0·89]; p=0·0021). The safety profile of sacituzumab govitecan was consistent with previous studies (including the TROPiCS-02 primary analysis and the ASCENT trial). One fatal adverse event (septic shock caused by neutropenic colitis) was determined to be related to sacituzumab govitecan treatment. - Interpretation - Sacituzumab govitecan demonstrated statistically significant and clinically meaningful benefit over chemotherapy, with a 3·2-month median overall survival improvement and a manageable safety profile. These data support sacituzumab govitecan as a new treatment option for patients with pretreated, endocrine-resistant HR+ and HER2- metastatic breast cancer. - Funding - Gilead Sciences.
Online veröffentlicht: 23. August 2023, Artikelversion: 19. Oktober 2023
Gesehen am 02.10.2024